Nguyen dynasty's implementation of international responsibility in the South China Sea (1802 - 1884) - Phuong, Nguyen Duy (Edelweiss Applied Science and Technology, 2025)
The South China Sea is one of the largest seas in the world. Vietnam owns up to 30% of the area of this sea. The Nguyen Dynasty unified the country and managed a large territory not only on land but also extending into the South China Sea in the 19th century. Inheriting the previous dynasties’ sea and island organization and management experience, the Nguyen Dynasty not only focused on protecting the national sovereignty of seas and islands but also demonstrated its increasing international responsibility. Having reviewed ancient documents, especially the Imperial Records of the Nguyen Dynasty (Châu bản Triều Nguyễn), and built upon the research achievements of domestic and foreign authors, while simultaneously applying two main historical research methods (historical and logical methods) along with other methods (systematic, analytical, synthetic, and comparative methods), the article focuses on analyzing and objectively evaluating the actions that demonstrate the international responsibility of this dynasty for peace and maritime safety in the South China Sea. In addition, it also shows that the Nguyen Dynasty made significant efforts in addressing maritime security challenges with many countries in the region and the world, as well as the relationship between national interests and international interests at that time.